Perengkahan Katalitik Palm Fatty Acid Distillate Menjadi Biofuel Menggunakan Katalis Fly Ash Sawit - Widya Pangestu; Yelmida Yelmida; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm fly ash is a solid waste from process of shell and fiber burning. Palm fly ash have many component such as potassium, sodium, and silica, that make it can to be use as a catalyst. Palm fatty acid distillate (PFAD) is a byproduct from process of making cooking oil. PFAD potentially to used to produce biofuel with catalytic cracking process because it has a long hydrocarbons chain.  This study aims to utilize PFAD to be raw material of making biofuel with palm fly ash as a catalyst, as well as to know component of biofuel produced. This research was conducted into two stages, namely preparation of catalyst and process of cracking. Cracking reaction carried out in a stirred tank reactor at a variation of temperature 370-4300C, variation of ratio feed/catalyst 100-250:1 g. Cracking process carried out for 120 minutes. Yield maximum product obtained at a temperature of 4100 C with ratio feed/catalyst 150:1 g and catalyst dimension -60+100 mesh that is equal to 57,14 Cracking results analyzed by GC-MS and found the biofuel produced more dominant is a constituent of gasoline fuel.   Keywords : Biofuel, Fly ash Sawit, Catalytic Cracking, PFAD